2010
DOI: 10.1038/eye.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of glaucoma following paediatric cataract surgery: a 20-year retrospective study

Abstract: Aims To analyse the incidence of glaucoma in children undergoing cataract surgery and determine whether early surgery is associated with increased risk of glaucoma. Methods A retrospective chart review of all children aged 14 years or less who had surgery for congenital or developmental cataract at one unit over the last 20 years. The children were divided into three groups; group 1 consisting of children aged p50 days at surgery, group 2 those aged 51 days to 1 year, and group 3 aged 1-14 years. Results We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
(45 reference statements)
1
21
1
4
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Oranlar arasındaki bu farklılık çalışmaya dahil edilen hasta gruplarının yaş ve takip sürelerinin farklı olmasına, tanı kriterlerine, katarakt dışı oküler ve sistemik anomalili hastaların çalışmaya dahil edilip edilmemesine ve cerrahi teknik farklılıklarına bağlı olabilmektedir. Ayrıca hastaların genellikle asemptomatik oluşu, göz içi basıncının ölçümü ve diğer muayenelerdeki zorluklar tanı koymayı güçleştirmektedir.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Oranlar arasındaki bu farklılık çalışmaya dahil edilen hasta gruplarının yaş ve takip sürelerinin farklı olmasına, tanı kriterlerine, katarakt dışı oküler ve sistemik anomalili hastaların çalışmaya dahil edilip edilmemesine ve cerrahi teknik farklılıklarına bağlı olabilmektedir. Ayrıca hastaların genellikle asemptomatik oluşu, göz içi basıncının ölçümü ve diğer muayenelerdeki zorluklar tanı koymayı güçleştirmektedir.…”
Section: Discussionunclassified
“…İnsidans, olguların özelliklerine ve takip süresinin uzunluğuna bağlı olarak %2 ile %58,7 arasında değişen oranlarda bildirilmektedir. [1][2][3][4][5][6][7][8][9][10][11][12][13] Konjenital kataraktlı olguların sadece ameliyat edilmiş gözlerinde ortaya çıkması, 2,14 glokom gelişimi için cerrahinin şart olduğunu göstermektedir. Cerrahinin trabeküler ağ üzerine etkilerini açıklamaya yönelik çeşitli teoriler 12,15 bulunmakla birlikte patogenez tam olarak bilinmemektedir.…”
Section: Gi Riflunclassified
See 2 more Smart Citations
“…5,6 In addition, some recent studies found that the earlier the surgical extraction of a pediatric cataract, the higher the risk for postcataract-extraction glaucoma, 7,8 independent of other factors, although other studies did not replicate this finding. 4,9,10 The use of intracameral dexamethasone has been found to significantly reduce the quantity of aqueous inflammatory cells in glaucomatous eyes and control eyes 1 day after phacoemulsification in adults while causing little risk for intraocular pressure (IOP) elevation. 11 Regarding corneal safety, dexamethasone was found to increase the sodium, K-ATPase activity, and pump function of cultured mouse corneal endothelial cells.…”
mentioning
confidence: 99%